Metodologia para projetos de engenharia natural em obras de infraestrutura - Maffra, Charles Rodrigo Belmonte (2014)
Soil bioengineering is a widespread science which is usually applied in Europe and North America for natural systems stabilization such as streambanks, slopes and eroded areas. It is a relatively new technical discipline, that has well developed concepts, from a practical point of view. Nevertheless, it still has some theoretical and technical issues that should be addressed. One of those issues is related with the lack of analytical methodologies and procedures for the elaboration of projects based on soil bioengineering techniques. Taking this issue into consideration, the purpose of this dissertation is to accomplish the development of a project methodology for the application of soil bioengineering techniques in infrastructure works, and to show its use in one case study for river stabilization in pipeline stream crossing. The developed methodology presents an hierarchical procedure with three project phases: conceptual, basic and executive, each of which is composed by objectives and development activities. During project elaboration this methodology has proved to be relevant to acquire, manage and analyze information in a rationalized sequence, and hence, facilitating the understanding of the problem phenomenology, the choice of techniques and the design method for each problem, as well as logistic description and quantification required for the execution of the one projected case study. This methodology has proved to be an efficient tool to standardize and generalize soil bioengineering project activities for greater responsibility applications.